"Corruption Networks and Implications For Ethical Corruption Reform" - Nielsen, Richard P. (Journal of business ethics, 2003)
The problem this article focuses on is not the isolated individual act of corruption, but the systematic, pervasive sub-system of corruption that can and has existed across historical periods, geographic areas, and political-economic systems. It is important to first understand how corrupt and unethical subsystems operate, particularly their network nature, in order to reform and change them while not becoming what we are trying to change. Twelve key system elements are considered that include case examples from Asia, Latin America, the Mediterranean, and North America. A key operating feature of corruption sub-systems is that they are relatively stable networks rather than exceptional, independent, individual events. Drawing on social network, social movement, and action-learning theories, six theory building propositions concerning ethical corruption reform are developed.